Fundamentals of the theory of operator algebras. - Kadison, Richard V., 1925- (Pure and applied mathematics (Academic Press), 1983)
The goal of this text is to teach operator algebras and lead readers to where the literature - in the subject specifically and in its applications - becomes accessible. The choice of material was made from among the fundamentals of what may be called the "classical" theory of operator algebras